Effects of Bacillus subtilis on the reduction of U(VI) by nano-Fe0. (15th September 2015) - Ding, Congcong; Cheng, Wencai; Sun, Yubing; Wang, Xiangke
Abstract: The effects of Bacillus subtilis ( B . subtilis, a typical model bacterium) on the reduction of U(VI) by nanoscale zero-valent iron (nano-Fe 0 ) were investigated using batch techniques. The reaction products were analysed using spectroscopic techniques, and a kinetics model was developed to elucidate the mechanisms of U(VI) reduction by nano-Fe 0 . The presence of B . subtilis enhanced the U(VI) sorption rate at pH 3.5–9.5 but inhibited the reduction rate of U(VI) to U(IV) at pH > 4.5. According to the FTIR and XRD analysis, the reduction of U(VI) to U(IV) was inhibited due to the formation of inner-sphere surface complexes between the oxygen-containing functional groups of B . subtilis or extracellular polymeric substances with the Fe(II)/Fe(III) generated by nano-Fe 0, which blocked electron transport from the Fe 0 core to U(VI). Based on the EXAFS analysis, a fitting of U–Fe shell at ∼3.44 Å revealed inner-sphere bidentate complexes between uranyl and the oxide film of nano-Fe 0 . For the nano-Fe 0  +  B. subtilis system, the U–Fe shell (at ∼3.44 Å) and the U–C/P shell (at ∼2.90 Å) further indicated the formation of inner-sphere surface complexes. The kinetics model supported that U(VI) reduction was triggered by U(VI) sorption on the oxide shell of nano-Fe 0 . The XPS and XANES analyses showed that reductive precipitation was the main mechanism of U(VI) removal by nano-Fe 0, whereas the sorption process dominated the removal of U(VI) in the presence of B . subtilis, which was further demonstrated by TEM images.